Structural characterization of modified whey protein isolates using cold plasma treatment and its applications in emulsion oleogels. (15th September 2021) - Gong, Wei; Guo, Xiao-lu; Huang, Hai-bo; Li, Xiang; Xu, Yu; Hu, Jiang-Ning
Highlights: Cold plasma has been successfully used in modification of whey protein isolates. Cold plasma significantly lowered the oil-water interfacial tension of WPI. The oleogels have porous networks with excellent antimicrobial activities. Abstract: Cold plasma as a green and expeditious tool was used to modify whey protein isolate (WPI) in order to improve its emulsion capability. The emulsion-based oleogels with antibacterial functions were then constructed using the modified WPI. The modified WPI treated with cold plasma under 10 s at 50 W power significantly lowered the oil-water interface tension. Meanwhile, the fluorescence intensity and the α -helix content of WPI reduced with the cold plasma treatment. It is noted that SEM results showed that the treated WPI had more regular dendritic structures. Such modified WPI was applied to construct oleogels loaded with thyme essential oil and coconut oil, which showed a porous uniform network structure and excellent antimicrobial activities against E.coli . As a proof of concept, this study demonstrated cold plasma could be as a new facile tool to modify food-sourced proteins and expected to enlarge their applications in oleogel productions.